Fotografi Dokumenter Kehidupan di Rumah Gadang - Herik . (Rekam: Jurnal Fotografi, Televisi, Animasi)
Supreme masterpiece born of a brilliant idea. That is the rationale aestetic. It should be added here, that a brilliant idea may not necessarily materialize into visual works good if not supported by means of casting ideas. As a nation that adheres to the philosophy of alam takambang jadi guru (natural surrounding is a teacher) they menyelarasi the natural order of life in a harmonious and dynamic, so that the theory of dialectical life called bakarano bakajadian (no cause and effect) that give rise to conflict and balance. Interest in the author of the Life Documentary Photography at The Rumah Gadang, because during this life or in the daily activities of life in the rumah gadang still retains the matrilineal system. Until now the system of matrilineal Minangkabau society due to the customs of the times, as they phrase and proverb-following proverb: “one big water, once the banks changed”. That is, that the customs rules they should be able to adapt to the motion of the times, in order to be preserved. Observation in the field corresponding author rumah gadang has encountered many homeowners who abandoned it, and now its existence has begun to decline, when seen from the rumah gadang cultural patterns have high historical value. In addition to setbacks against the rumah gadang itself is also a change 244 Fotografi Dokumenter Kehidupan di Rumah Gadang in the culture of matrilineal Minangkabau society. Creation of Life Documentary Photography in the rumah gadang to document the activity that once existed in the rumah gadang, where the longer presence of the rumah gadang is lost because of the very rapid development of time and lead to a modern society. The creation of this work also functioned for scientific research as well as useful for future purposes.Keywords: documentary photography, ideational, conceptual.